2019
DOI: 10.3390/nu11102432
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Skeletal Muscle Glucose Transport and Glucose Metabolism by Exercise Training

Abstract: Aerobic exercise training and resistance exercise training are both well-known for their ability to improve human health; especially in individuals with type 2 diabetes. However, there are critical differences between these two main forms of exercise training and the adaptations that they induce in the body that may account for their beneficial effects. This article reviews the literature and highlights key gaps in our current understanding of the effects of aerobic and resistance exercise training on the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 209 publications
(221 reference statements)
2
106
0
2
Order By: Relevance
“…Interestingly, in humans, intensive exercise training (6 weeks of cycling) was reported to increase the abundance of GLUT12 protein in vastus lateralis muscle by a factor of 2, implicating that GLUT12-mediated glucose transport in skeletal muscle might be of physiological relevance, at least under trained conditions [224]. In addition to improvements in skeletal muscle glucose transport [64,187], exercise has profound beneficial effects on insulin sensitivity at many different sites of insulin action, in particular in the insulin-resistant and diabetic state [192].…”
Section: Physical Exercise Improves Glycemic Control Through Enhancinmentioning
confidence: 99%
“…Interestingly, in humans, intensive exercise training (6 weeks of cycling) was reported to increase the abundance of GLUT12 protein in vastus lateralis muscle by a factor of 2, implicating that GLUT12-mediated glucose transport in skeletal muscle might be of physiological relevance, at least under trained conditions [224]. In addition to improvements in skeletal muscle glucose transport [64,187], exercise has profound beneficial effects on insulin sensitivity at many different sites of insulin action, in particular in the insulin-resistant and diabetic state [192].…”
Section: Physical Exercise Improves Glycemic Control Through Enhancinmentioning
confidence: 99%
“…Exercise can improve insulin sensitivity and thereby alter skeletal muscle glucose transport and maintain blood glucose homeostasis, especially for patients with metabolic disease [ 36 ], but may not always have the same effect in athletes due to excessive production of ROS during exercise training [ 37 , 38 , 39 ]. In this study, we did not detect a significant reduction in glucose parameters in the ubiquinone group after supplementation; however, we found that athletes with higher WBC ubiquinone level (≥0.5 nmol/g) showed improved glycemic control ( Table 3 and Figure 2 ), which might be related to an increase in antioxidant capacity ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is considered to be a metabolic organ, which consumes a lot of energy and plays an important role in supporting exercise capacity and regulating body fat mass and blood glucose levels. Skeletal muscles take up glucose and control blood glucose levels and play an important role in storing glucose as glycogen [ 63 , 64 ]. Skeletal muscle has also been found to have a role as an endocrine organ secreting myokine (physiologically active substance) and regulating organ function throughout the body [ 65 , 66 ].…”
Section: Dysbiosis and Sarcopenia From The Viewpoint Of Nutritionmentioning
confidence: 99%